(untitled) (TAMADDUN NURI JURNALI, 2025)
This article explores synergetics as an interdisciplinary scientific paradigm that has found wide application in philosophy. The author analyzes the fundamental principles of synergetics, its influence on contemporary philosophical thought, as well as the methodological features of applying the synergetic approach to the understanding of complex systems. It is shown that synergetics contributes to the rethinking of traditional philosophical categories — order, chaos, self-organization, and development.